New species of Binodacarus and Rhodacarus mites (Mesostigmata: Rhodacaridae) from Brazilian Cerrado biome, and a key to the world species of the genera - Braga, Alice Freitas; Castilho, Raphael De Campos (Zootaxa, 2024)
Binodacarus tocantinensis sp. nov. and Rhodacarus emilianoi sp. nov. are described based on the morphology of adult females collected from litter/soil in a fragment of the Cerrado biome, in Tocantins state, northern Brazil. In addition, the keys for the separation of females of the world species of Binodacarus and Rhodacarus are provided.